Determining factors for the choice of islamic insurance / Faizah Azzam Ahmad Azzam - Ahmad Azzam, Faizah Azzam (2004)
The Islamic Insurance system is gaining momentum The Islamic insurance (Takaful) industry had been experiencing double digit growth for more than a decade Although the Takaful industry had made its mark and the growth has been significant, the industry still remains relatively small when compared to conventional insurance. The Islamic insurance system is expected to face strong competition not only from conventional insurance companies but also from well-established conventional banks that are offering Islamic insurance product, hi this study, an attempt is made to determine the factors that hinder the customers from choosing the Islamic insurance product. A sample of 100 respondents took part in this study. The influence of demographic factors such as gender, age, marital status, race, religion, qualification and monthly income on choice of Islamic insurance indicated that age is among factors that determine the consumer choice of insurance. Majority of the respondents that subscribe Islamic and conventional insurance were in the age of 31 to 40 years old. The older generation is more likely to have an insurance policy. Also, the study indicated that majority of the demand for insurance policy came from the married couple because his financial status is normally more stable. In analyzing the twenty-five factors, one sample test was used to find out the probable reasons that can influence the customer for not choosing Islamic insurance. The analysis of the respondents revealed thirteen main factors for the low participation in Islamic insurance product. Among the factors were; the public was not offered Islamic motor insurance policy when purchasing new vehicle, marketing of Islamic insurance scheme was not that aggressive as conventional insurance scheme, the public has a low level of knowledge about Islamic insurance scheme and very few branches available throughout the country. As such, the researcher believes that Takaful operators should put more aggressive effort in educating the public through the mass media by emphasizing more on the benefits of Islamic insurance as compared to conventional insurance.